Indices and methods for evaluating gross ecosystem product in sea areas: a case study in Changdao County, China - Li, Wenwen; He, Shuai; Chen, Erwen; Xia, Tao; Jin, Yuemei; Tang, Boping; Chen, Shang (Frontiers in Marine Science, 2024)
Introduction Coastal nations heavily rely on their sea areas to achieve sustainable socioeconomic development. Sea areas offer abundant marine ecosystem products and services that are difficult to substitute with industrial goods. Although considerable research has been performed to evaluate the contribution offrom the marine ecosystems to human well-being, systematic and measurable indices are lacking. Methods To address this knowledge gap, ecosystem service theory was used to establish a framework for assessing the gross ecosystem product (GEP) of a sea area, which represents the total monetary value of final ecosystem products directly and indirectly used by people within a specific administrative jurisdiction in one year. To evaluate marine GEP, three primary indices, i.e., material products, regulating products, and cultural products, were employed, and they consist of eight secondary indices. Material products in the sea area include aquatic products and oxygen products; regulating products include carbon sequestration, climate regulation, waste treatment, and coastal protection; and cultural products include leisure and recreation, and seascape-added value. The marine GEP was calculated for the administrative sea areas of Changdao County, which is located in the Yellow Sea-Bohai Sea transitional zone. Results and discussion Our analysis indicated that from 2017 to 2019, the marine GEP in Changdao ranged between 32.59 and 33.35 billion Chinese yuan (CNY). Regulating products contributed two-thirds of this total value. However, over the three-year period, the marine GEP underwent a 5.64% decrease in Changdao. Specifically, the value of material products increased by 38.85% while that of regulating and cultural products decreased by 9.16% and 15.87%, respectively. Notably, the spatial distribution of ecosystem product values in Changdao displayed two prominent trends: (1) higher values along the coastal sea areas of islands and lower values in offshore sea areas; and (2) higher values in coastal areas of southern islands and lower values in coastal areas of northern islands. Marine GEP may serve as a comprehensive indicator for assessing the sustainability of marine ecosystem. Combining the assessment of both marine and terrestrial GEP facilitates an understanding of how marine and terrestrial ecosystems interact in coastal regions. Furthermore, the combined use of marine GEP and GDP helps better evaluate and sort the level of green development of coastal nations and regions.